Angiographic findings and survival in patients undergoing coronary angiography due to sudden cardiac arrest in Western Sweden. (May 2015) - Redfors, Björn; Råmunddal, Truls; Angerås, Oskar; Dworeck, Christian; Haraldsson, Inger; Ioanes, Dan; Petursson, P.; Libungan, Berglind; Odenstedt, Jacob; Stewart, Jason; Robertsson, Lotta; Wahlin, Magnus; et al.
Abstract: Aim: Sudden cardiac arrest (SCA) accounts for more than half of all deaths from coronary heart disease. Time to return of spontaneous circulation is the most important determinant of outcome but successful resuscitation also requires percutaneous coronary intervention in selected patients. However, proper selection of patients is difficult. We describe data on angiographic finding and survival from a prospectively followed SCA patient cohort. Methods: We merged the RIKS-HIA registry (Register of Information and Knowledge about Swedish Heart Intensive Care Admissions) and SCAAR (Swedish Coronary Angiography and Angioplasty Registry) for patients hospitalized in cardiac care units in Western Sweden between January 2005 and March 2013. We performed propensity score-adjusted logistic and Cox proportional-hazards regression analyses on complete-case data as well as on imputed data sets. Results: 638 consecutive patients underwent coronary angiography due to SCA. Severity of coronary artery disease was similar among SCA patients and patients undergoing coronary angiography due to suspected coronary artery disease ( n = 37, 142). An acute occlusion was reported in the majority of SCA patients and was present in 37% of patients who did not have ST-elevation on the post resuscitation ECG. 31% of SCA patients died within 30 days. Long-term risk of death among patients who survived the first 30 days was higher in patients with SCA compared to patients with acute coronary syndromes ( P < 0.001). Conclusions: Coronary artery disease and acute coronary occlusions are common among patients who undergo coronary angiography after sudden cardiac arrest. These patients have a substantial mortality risk both short- and long-term.